Beyond Commercial ERP: A Mixed-Methods Analysis of Challenges and Efficiency Gains from an Internally Developed Kanban System in Pharmaceutical Production - Faiz Ardani, Ahmad; Ratih Hendayani (CITACONOMIA : Economic and Business Studies, 2025)
This study examines the implementation and impact of an internally developed ERP-based Kanban system in a pharmaceutical company as a cost-effective alternative to commercial ERP. Utilizing a mixed-methods case study, the research first applied Interpretive Structural Modeling (ISM) to structure key implementation challenges, followed by a quantitative comparative analysis of operational efficiency. Findings reveal a six-level hierarchy of challenges, identifying "Lack of Top Management Vision and Leadership" as the fundamental driver. Equally important is the finding that “High initial investment cost” exhibited minimal driving power. The system achieved transformative efficiency gains, reducing data input time by 98.4% and data analysis time by 73.9%. The study provides an original, empirically validated model of implementation barriers and demonstrates that internal development is a viable, high-return strategy for SMEs in regulated industries, enabling enhanced compliance and data-driven decision-making.